The Existence of Mosques In Community Economic Empowerment During The Covid-19 Pandemic - Arif Widodo Nugroho; Aisyah Pia Asrunputri; Herwin Kurniawan; Toto Tohari (Syntax Corporation, 2022)
The COVID-19 pandemic that hit around the world also greatly impacted the economy of the community, especially in Indonesia. The role of the Mosque which is only limited to places of worship was, back as the time of the Prophet, where not only a place of worship but also as a place of economic empowerment of the ummah. This research was conducted to see the extent of the role of mosques under the auspices of Muhammadiyah in empowering the economy of the ummah. This research is a qualitative study, using primary data collected then developed for the in-depth interview process to the board of Muhammadiyah Regional Leader (PDM) East Jakarta and the administrator of Muhammadiyah Assudairi Mosque. The findings obtained are the role of Assudairi Mosque itself not only as a place to worship, but a place that provides faith and trust for its worshippers to provide assistance and charity that will be distributed to other worshippers and citizens who need help, especially in terms of the economy. The role of PDM itself is very active in developing Muhammadiyah Business Charity (AUM) in providing assistance to MSMEs, so that people during the Covid-19 pandemic are able to be independent in finding a decent livelihood.